Development of Pesantren Curriculum Through The Ke-Takhassusan Program At MTs Ma’arif Gondang Watumalang Wonosobo - Rifai, Rizal; Kamal, Faisal; Fatiatun, Fatiatun (DAS Institute, 2025)
This article examines the development of a pesantren-based curriculum through the ke-takhassusan program implemented at MTs Ma’arif Gondang Watumalang, Wonosobo. The program emerged as a response to the need for strengthening religious education in the post-COVID-19 period, during which students experienced a significant decline in religious engagement. This study aims to describe the strategies of the ke-takhassusan program, analyze its benefits and challenges, and assess its implications for enhancing the madrasah curriculum. The research employed a qualitative approach using interviews, observations, and documentation as data collection techniques. The findings reveal that the program is implemented systematically with core materials such as fiqh, tajwid, nahwu, shorof, classical Islamic texts, and akhlak, utilizing traditional pesantren methods like sorogan and bandongan. The program positively impacts students’ religious literacy, shapes their religious character, and fosters a more Islamic school environment. Despite facing challenges such as student fatigue, monotonous methods, and limited facilities, the program significantly contributes to contextual and practical Islamic education in the madrasah system.